Advances in pharmaceutical education: an experience with the development and implementation of an Objective Structured Clinical Examination (OSCE) in an undergraduate pharmacy program - Awaisu, Ahmed; Nik Mohamed, Mohamad Haniki (International Pharmaceutical Federation (FIP), 2010)
The objective of this paper is to describe how a hybrid-OSCE was developed and applied to an undergraduate clinical pharmacy course as a pilot for assessing clinical competence in a Malaysian university; to present some of the instruments utilized for the conduct and assessment of the examination; and to evaluate the performance of the students in the OSCE. A seven-station OSCE (five live and two rest stations) was designed and implemented to accomplish the learning objectives of the clinical pharmacy course(s) as enshrined in our bachelor of pharmacy curriculum. The key processes involved in designing and implementing the OSCE include: development of a blueprint which served as a guideline; development and face-validation of the seven stations in accordance with the blueprint; design of dichotomous performance checklist/assessment instruments for individual stations; feasibility/pilot testing and rehearsals at OSCE stations; and conduct of the final examination. The broad competencies tested in the OSCE included patient counselling and communication, identification and resolution of drug-related problems (DRPs) using evidence-based approach, and literature evaluation/drug information provision. The students scored the highest marks in insulin delivery devices counselling station (mean ± SD=17.6±3.1), followed by DRPs identification/resolution and warfarin counselling stations with mean ± SD of 17.36±2.7 and 16.9±2.2, respectively. Examinees also scored the least in the drug information station (mean ± SD=15.55±3.8). There were statistically significant differences between students’ performances at the individual OSCE stations (F=3.698; p=0.012). The study revealed that undergraduate pharmacy students were better in performing patient counselling and identification/ resolution of DRPs than in the drug information task. The design and implementation of the OSCE among fourth-year BPharm students was technically feasible and a great success.